BUDAYA POSITIF DALAM PENGEMBANGAN KINERJA GURU DI SMA NEGERI 2 PERCUT SEI TUAN - Br. Depari, Risma Dewi; Isman, Muhammad; Siregar, Astri Novia (EDUTECH, 2024)
This research aims to determine: (1) teacher performance at SMA Negeri 2 Percut Sei Tuan; (2) positive culture at SMA Negeri 2 Percut Sei Tuan; (3) strategies for building, developing, maintaining sustainability and consistent implementation of a positive culture; and (4) what is the relationship between positive culture and teacher performance at SMA Negeri 2 Percut Sei Tuan.The type of this research is qualitative research with a case study approach. The data collection techniques used were interviews, observation and documentation. The analysis techniques used are data reduction, presentation and conclusions. The subjects and objects of the research were the principal and teachers at SMA Negeri 2 Percut Sei Tuan. The results of the research show that: (1) The performance of teachers at SMA Negeri 2 Percut Sei Tuan can be categorized as "good", this is shown through the teacher's ability to plan, to implement and to assess learning outcomes, well as the ability to guide and train students and carry out additional tasks mandated by the school; (2) The positive culture at SMA Negeri 2 Percut Sei Tuan has been good implemented, they are the culture of togetherness for formulating the vision, mission and goals of the school , the culture of collaborating of teachers in developing and implementing the curriculum, the culture of the school community being committed and consistent in building better communication, positive and mutually supportive, the culture of the school community together building a positive narrative about the school and also the school leaders and figures, the culture of transparency shown by school management in building the organizational structure and the commitment of the school community to implement the organizational structure, the culture of togetherness implement the positive ritual at the school, a culture of collaboration of teacher in learning and designing learning, and culture of school residents who often build good relationships and interactions with school stakeholders; (3) SMA Negeri 2 Percut Sei Tuan has made efforts to build and develop a positive culture using various strategies; and (4) The positive culture that is developed at SMA Negeri 2 Percut Sei Tuan has a positive influence on increasing teacher performance